2022
DOI: 10.1016/j.envres.2021.112367
|View full text |Cite
|
Sign up to set email alerts
|

Greenspace and park use associated with less emotional distress among college students in the United States during the COVID-19 pandemic

Abstract: The COVID-19 pandemic has negatively affected many people's psychological health. Impacts may be particularly severe among socially vulnerable populations such as college students, a group predisposed to mental health problems. Outdoor recreation and visits to greenspaces such as parks offer promising pathways for addressing the mental health challenges associated with COVID-19. During the early stages of the pandemic (March–May 2020), we surveyed 1280 college students at four large public universities across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 110 publications
3
62
0
Order By: Relevance
“…This is consistent with research suggesting that the well-being markers returned to pre-pandemic levels by the fall of 2020 [30]. Moreover, some studies indicate that the participants were not spending more time in nearby greenspaces [54,55]. For example, students from four universities in the United States reported that they were limiting their park use in order to avoid people, to reduce the threat of contracting COVID-19, or because of restrictions beyond their control [54].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is consistent with research suggesting that the well-being markers returned to pre-pandemic levels by the fall of 2020 [30]. Moreover, some studies indicate that the participants were not spending more time in nearby greenspaces [54,55]. For example, students from four universities in the United States reported that they were limiting their park use in order to avoid people, to reduce the threat of contracting COVID-19, or because of restrictions beyond their control [54].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, some studies indicate that the participants were not spending more time in nearby greenspaces [54,55]. For example, students from four universities in the United States reported that they were limiting their park use in order to avoid people, to reduce the threat of contracting COVID-19, or because of restrictions beyond their control [54]. Despite this, the people who did report spending more time in greenspaces were more likely to report higher senses of well-being (through life satisfaction and subjective happiness) [55] and lower emotional distress [54], which is similar to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is also encouraging from the public health perspective that amidst one of the more challenging periods in recent history, that a new group of U.S. outdoor recreationists (20%) have emerged during the pandemic, likely benefiting from the health outcomes they receive from these activities [16][17][18][19][20]28]. This creates a tremendous opportunity to engage this group of new recreationists in life-long healthy recreation and conservation behaviors that promote the preservation of the resources, sustaining outdoor recreation.…”
Section: Discussionmentioning
confidence: 99%
“…Motivations for pursuing outdoor recreation during this period have been largely driven by needs associated with personal health and well-being [15], such as relieving stress and supporting mental health, and facilitating physical health through outdoor exercise [16]. And, research in the U.S. indicates that outdoor recreation during the pandemic has in fact, led to improved mental health outcomes [17,18]. Similar health-related trends have been discovered internationally [5,19,20].…”
Section: Introductionmentioning
confidence: 91%